1980
DOI: 10.1002/pssa.2210580218
|View full text |Cite
|
Sign up to set email alerts
|

Disorder in KNiCl3 as observed by electron diffraction

Abstract: KNiCl3 crystals are studied by means of electron diffraction. Only a small part of the crystals is found to be well ordered in the known room‐temperature structure, as most crystals exhibited diffuse streaking along the [10.0] and [11.0] directions of the reciprocal space. Weak extra reflections, occasionally observed instead of the diffuse streaking are attributed to an orthorhombic structure, related in a simple way to the room‐temperature structure, determined by X‐ray analysis and neutron powder diffractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Fitting to the intensities of x-ray single-crystal scattering indicates that in different parts of the crystal the amplitude of the shift varies from 0.21 to 0.93 Å [9]. Additional evidence for such disorder in the crystal structure was obtained by electron diffraction [10]. We will refer to this structure, associated with the 561 K phase transition, as the room temperature (RT) structure.…”
Section: Introductionmentioning
confidence: 99%
“…Fitting to the intensities of x-ray single-crystal scattering indicates that in different parts of the crystal the amplitude of the shift varies from 0.21 to 0.93 Å [9]. Additional evidence for such disorder in the crystal structure was obtained by electron diffraction [10]. We will refer to this structure, associated with the 561 K phase transition, as the room temperature (RT) structure.…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation for the large mosaic spread and poor crystal quality at high values of x may be found in the structural phase transition of RbFeBr,. The electron diffractionmeasurements of Visser and Prodan (1980) showed that this type of structural phase transition in ABX, compounds from P6,/mmc to P6,cm symmetry is accompanied by a large increase in structural disorder. The introduction of small amounts of C1-to RbFeBr, may help to trigger such disorder by acting as nucleating points for structural domains.…”
Section: Data Analysis Proceduresmentioning
confidence: 97%
“…The new crystal structure is that of KNiC1, at room temperature (Visser et a1 1980) with space group P6,cm and the cell parameters a and b enlarged by a factor of v 3 . ABX, crystals undergoing phase transitions of this sort have been shown to possess structural disorder in the P6,cm phase (Visser and Prodan 1980). The structural parameters of RbFeC1, and RbFeBr, are given in table 1.…”
Section: Properties Of a F E X Magnetsmentioning
confidence: 99%
“…[6][7][8] Lattice distortions of KNiCl 3 family compounds are characterized by -BX 3 -chain shifts along the c-axis. 9,10) Representatives of these compounds are KNiCl 3 [11][12][13][14][15][16][17] and RbMnBr 3 , [18][19][20][21][22] whose room-temperature (RT) structure has triplicated ( √ 3a× √ 3a × c; a and c are lattice constants of the prototype CsNiCl 3 -structure) unit cells with chain shifts along the c-axis in an up-up-down manner, as shown in Fig. 1(a).…”
Section: Introductionmentioning
confidence: 99%
“…This phase is called phase III and the structure, sometimes called the 'RT-KNiCl 3 -structure', was reported to take symmetries of the space group P 6 3 cm. However, it was not excluded by diffraction analysis 11,12) that the phase III structure may be another one with P 3c1 symmetry characterized by up-0-down type chain shifts, as shown in Fig. 1(b).…”
Section: Introductionmentioning
confidence: 99%